Product Innovation And Digital Marketing Strategies To Improve The Competitiveness Of MSMEs: Case Study On MSME " Dhany Bakery” In Jombang Regency - Afif Nur Rokhman; Sudarmiatin; Puji Handayati; Naswan Suharsono (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The development of digital technology has a significant impact on MSME business patterns, especially in marketing and product innovation aspects. This case study aims to analyze the strategy of product innovation and the use of digital marketing at SMEs “Dhany Bakery” and its influence on improving business competitiveness. The research method uses a qualitative approach through direct observation, in-depth interviews, and documentation. The results showed that product innovation focusing on flavor and packaging variations and the implementation of digital marketing through Instagram, WhatsApp Business, and TikTok Shop were able to increase brand awareness and sales by 35% in three months. This study provides a practical contribution to other MSMEs to improve competitiveness through the use of digitization.